2016
DOI: 10.1113/jp273115
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic vesicle pool‐specific modification of neurotransmitter release by intravesicular free radical generation

Abstract: Earlier studies suggest that spontaneous and evoked neurotransmitter release processes are maintained by synaptic vesicles which are segregated into functionally distinct pools. However, direct interrogation of the link between this putative synaptic vesicle pool heterogeneity and neurotransmission has been difficult. To examine this link, we tagged vesicles with horseradish peroxidase (HRP) - a haem-containing plant enzyme - or antibodies against synaptotagmin-1 (syt1). Filling recycling vesicles in hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…eHRPsyt1 was targeted to the lumen of SVs and when a SV fused with the plasma membrane, extracellular hydrogen peroxide was cleaved and the radicals rendered the released SV dysfunctional. With this technique it was possible to dissect SV cycling in physiological experiments [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…eHRPsyt1 was targeted to the lumen of SVs and when a SV fused with the plasma membrane, extracellular hydrogen peroxide was cleaved and the radicals rendered the released SV dysfunctional. With this technique it was possible to dissect SV cycling in physiological experiments [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note, however, that some antibodies might affect protein distribution and trafficking in live cells. Thus, rabbit polyclonal antibodies against the luminal domain of synaptotagmin 1 have been suggested to alter synaptic function (Afuwape et al, 2017). At the same time, mouse antibodies against the same target, which are usually used for vesicle tracking experiments (Matteoli et al, 1992; Kraszewski et al, 1995; Sara et al, 2005; Fernández-Alfonso et al, 2006; Wienisch and Klingauf, 2006; Hua et al, 2010), have not been reported to have such an effect, and do not perturb vesicle trafficking even when used for several days (Truckenbrodt et al, 2018b).…”
Section: Methodsmentioning
confidence: 99%
“…However, this approach is not free of potential controversies. Synaptotagmin 1 antibodies have been in use for more than two decades 10,11 and they do not appear to impair synaptic function 8,12 , but a significant modulation of vesicle recycling via the antibodies has been recently noted 13 . Thus, the usage of such antibodies is likely to provide a realistic image of the vesicle protein organization after exocytosis, but may have some modulatory side effects.…”
Section: Introductionmentioning
confidence: 99%